Hubungan tingkat pengetahuan tentang kesehatan gigi dan mulut dengan tingkat kebersihan gigi dan mulut anak sekolah dasar - Yuniarly, Etty; Amalia, Rosa; Haryani, Wiworo (Poltekkes Kemenkes Yogyakarta, 2019)
Dental and oral health issues are an important concern in health development, one of which is caused by vulnerable groups of school-aged children from dental health disorders. School age is age important in growth and physical development of the child. This period is also known as a critical period because at this time the children start developing habits that usually tend to settle into adulthood. One of them is the habit of maintaining oral hygiene. This research aims to find out the level of knowledge on oral health and the level of oral hygiene elementary school children. This research use analytic observational approach cross sectional (cut the latitude) is a design by doing observations at the same time. This research was carried out in primary schools of the country Tuguran sub-district of Sleman Regency Limestone Daerah Istimewa Yogyakarta. Total sample of 60 children of class III, IV, and V were taken with purposive sampling method. Data collection using the questionnaire and examination of oral hygiene. Data analysis techniques using correlation analysis Pearson Product Moment test. The number of class III, IV, and V SD Negeri Tuguran have the level of knowledge on oral health good categories as many as 51.7% and level of oral hygiene medium category as much as 55%. The results of the calculation of statistical analysis with Pearson Product Moment test by using a confidence level of 95% (? = 0.05) obtained results of ?-value = 0.000, because ?-value < ? then the Ho rejected and accepted Ha. There was a relationship of the level of knowledge on oral health with the level of oral hygiene in elementary school children.